2021
DOI: 10.18632/aging.203354
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with C16 peptide and angiopoietin-1 confers neuroprotection and reduces inflammation in 3-nitropropionic acid-induced dystonia mice

Abstract: Dystonia is a disorder associated with abnormalities in many brain regions including the basal ganglia and cerebellum. The toxin 3-Nitropropionic acid (3-NP) can induce neuropathologies in the mice striatum and nigra substance, including excitotoxicity, neuroinflammation, and extensive neuronal atrophy, characterized by progressive motor dysfunction, dystonia, and memory loss, mimicking those observed in humans. We established a mouse model of dystonia by administering 3-NP. Given the reported neuroprotective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Iba-1 is a selective microglial marker protein that reflects active microglial cells [ 69 ]. Our results indicated that 3-NP dramatically elevated the expression of Iba-1 + microglia and alters the expression/release of the pro-inflammatory factors, TNF-α, IL-1β, IL-6, and NF-κB, which is corroborated by several studies [ 70 73 ]. After treatment with PIO or TEL, we detected the repression of these inflammatory factors as a result of inhibition of both striatal microglial cells and NF-κB expression.…”
Section: Discussionsupporting
confidence: 88%
“…Iba-1 is a selective microglial marker protein that reflects active microglial cells [ 69 ]. Our results indicated that 3-NP dramatically elevated the expression of Iba-1 + microglia and alters the expression/release of the pro-inflammatory factors, TNF-α, IL-1β, IL-6, and NF-κB, which is corroborated by several studies [ 70 73 ]. After treatment with PIO or TEL, we detected the repression of these inflammatory factors as a result of inhibition of both striatal microglial cells and NF-κB expression.…”
Section: Discussionsupporting
confidence: 88%
“…Several agents that aim to suppress the infiltration of leukocytes and the activation of macrophages/microglia in the CNS have been developed as potential therapies for MS (Cai et al., 2018 ). The effects of the compounds of C16 and Ang-1 on CNS inflammatory-related diseases have been confirmed using a variety of animal models (Han et al., 2010 ; Aarts et al., 2017 ; Chen et al., 2019 ; Nakazato et al., 2020 ; Fu et al., 2021 ). Both at the peak (2 weeks pi) and later stage (4 weeks pi) of disease course, the C + A, nano-carrier C + A, or fMLP-nano-carrier C + A compounds reduced the number of CD14 + monocytes, CD68+ macrophages, CD45+ leukocytes, and CD4+ T lymphocytes, with the largest differences seen in the fMLP-nano-carrier C + A treatment group.…”
Section: Discussionmentioning
confidence: 92%